Adverse and Advantageous Selection in the Laboratory - Ali, S. Nageeb; Mihm, Maximilian; Siga, Lucas; Tergiman, Chloe (American Economic Review, 2021)
We study two-player games where one-sided asymmetric information can lead to either adverse or advantageous selection. We contrast behavior in these games with settings where both players are uninformed. We find stark differences, suggesting that subjects do account for endogenous selection effects. Removing strategic uncertainty increases the fraction of subjects who account for selection. Subjects respond more to adverse than advantageous selection. Using additional treatments where we vary payoff feedback, we connect this difference to learning. We also observe a significant fraction of subjects who appear to understand selection effects but do not apply that knowledge. (JEL C92, D82, D91)